Diverse patterns of responsiveness to fine temporal features of acoustic signals in a temperate austral forest frog, Batrachyla leptopus (Batrachylidae). Issue 2 (4th March 2022) - Penna, Mario; Solís, Rigoberto; Moreno-Gómez, Felipe N.
ABSTRACT: Phonotactic female and vocal male responses of frogs to advertisement calls have been shown to encompass broader ranges than those of variation of natural mate-attracting signals. Anuran aggressive calls contribute to expand the range of sound features significant for communication. Evoked vocal responses (EVRs) of males of Batrachyla leptopus to synthetic advertisement calls and variants with different temporal features altered parametrically were studied to assess their correspondence with features of natural signals. Frogs responded to stimuli differing in note rate with vocal patterns that depended on the design of the synthetic sounds: lower call rates were obtained with stimuli composed of notes with linear rise-fall times deviating from the average of this parameter for natural calls. However, opposite results were obtained with stimuli composed of sinusoidally amplitude-modulated notes. Calls of longer duration resembling aggressive calls were emitted in response to low note rate sinusoidal stimuli. Stimuli with note durations above and below the natural average, stimuli having low pulse rates and a continuous tone also elicited longer calls of aggressive type. These patterns relate the vocal responses recorded to recognition of conspecific and heterospecific advertisement and aggressive calls, as well as to novel signal features.